Emerging optofluidic technologies for biodiagnostic applications. Issue 4 (14th March 2021) - Wu, Jiandong; Dai, Bo; Li, Zhenqing; Pan, Tingrui; Zhang, Dawei; Lin, Francis
Abstract: The unprecedented global COVID‐19 pandemic strongly argues the critical need for innovative diagnostic tools meeting the requirement of test speed, accuracy, and throughput. Owing to the integration of optics and microfluidics technologies, optofluidic technology enables highly precise flow manipulation and highly sensitive signal detection at the microscale, thus offering the promising potential for developing biodiagnostic applications. Research toward this direction is fast growing into an emerging area. In this paper, we give an overview of emerging optofluidic technologies for biodiagnostic applications with the focus on three common types of biomarkers: nucleic acid, protein, and cell. We conclude by discussing the challenges, opportunities, and future perspectives of this field. Abstract : Due to its extraordinary functions in fluidic control and signal detection, optofluidic technology has shown great potential in the development of biodiagnostic applications. This paper summarizes the emerging optofluidic technologies in this direction, focusing on three common types of biomarkers: nucleic acid, protein, and cell.